Nucleus Basalis Magnocellularis and Substantia Innominata Corticopetal Cholinergic Lesions Attenuate Freezing Induced by Predator Odor. - Knox, Dayan; Brothers, Holly; Norman, Greg J.; Berntson, Gary G. (Behavioral Neuroscience, 2008)
Previous studies have demonstrated that corticopetal cholinergic lesions applied to the nucleus basalis magnocellularis and substantia innominata (NBM/SI) attenuate operant suppression induced by aversive events. However, these lesions have no effect on open-arm behavior in the elevated plus-maze or changes in startle reactivity induced by bright light. This raises the possibility that NBM/SI corticopetal cholinergic lesions alter operant behavior and/or appetitive state, as opposed to the aversive state operant suppression is supposed to index. To address this concern, the authors documented the effect of NBM/SI corticopetal cholinergic lesions on freezing induced by a component of fox feces (2,4,5-trimethylthiazoline [TMT]), a paradigm that does not involve food deprivation or operant performance. TMT presentation induced freezing behavior, and this effect was attenuated by NBM/SI corticopetal cholinergic lesions. Because predator odor presentation, but not presentation of a predator, induces defense behaviors that are sensitive to anxiolytic drugs, the results of the study suggest that NBM/SI corticopetal cholinergic lesions attenuate anxiety-like states. Reprinted by permission of the publisher.